Kultur Ilmu Alquran di Jawa: Studi Kitab Al-Murshid al-Wajiz fi ‘Ilm al-Qur’an al-‘Aziz - Muhammad Fathur Rozaq (Jurusan Tafsir Hadis Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2019)
The article provides an analysis of the book Al-Murshid al-Wajiz fi ‘Ilm al-Qur’an al-‘Aziz written by Muhammad Shaleh Darat. The book was written in Javanese language and having such a concise content compared to other Qur’anic science books. I assume that this kind of summarization process cannot be detached from the author’s consideration of his own context in its age. The thought has relied upon his milieu in compiling the book, including the texts he reads and the context that surrounds him which cannot be separated from his standpoint. It then necessitates the transmission and transformation, perceiving the bulk of knowledge and reactualizing it into the work. In this work, I examine its transmission and transformation right after elucidating the social conditions at that time. Further, I consider about the new culture of Qur’anic theory and trace it by sociological approach.